Study on the Performance of Kenaf Fiber to Strengthening of Reinforced Concrete Beams: Review Paper - Hammood, Rasheed Abed; Sharifah Maszura, Syed Mohsin (American Association for Science and Technology., 2018)
This paper presents the findings of studies that were conducted on the effects of kenaf fiber on the mechanical properties of kenaf fiber reinforced concrete beams. In recent years, kenaf fiber reinforced concrete have been widely used as reinforcement system for concrete structures. Fibers are generally used as resistance of cracking and strengthening of concrete, therefore, kenaf fiber as material mainly used to strengthening the reinforced concrete. The aim of this paper is to review the work carried out using kenaf fiber as reinforcement in reinforced concrete to improving the strength properties of the concrete structures.